An ironic success: Walter E. Dandy and the invention of surgical treatment for intracranial aneurysm - Kang, Brandon Jun Hong (Nanyang Technological University, 2023)
A deadly and silent disease, brain aneurysms is one of the leading causes of deaths in the world today. Fortunately, this disease can be cured via surgery. The surgical therapy, also known as the clipping method, was first invented by Dr. Walter Dandy in 1935. Hailed as a revolution in neurosurgery, the cure is being used extensively by surgeons all over the world today. The invention of this cure has also elevated Dandy’s status within the medical community with some seeing him as a “hero of medicine”. However, was the invention of the cure an “inevitable consequence” of medical progress? Through locating the invention of the clipping method in early twentieth century America, this paper hopes to reconstruct the social, cultural and intellectual milieu in which Dandy developed his cure. Through the theme of “control” I argue that the invention of the clipping method be seen as an ironic progress marked with notions of personal rivalry and medical racism. Seen in this light, I hope to contribute to the present historical scholarship of the history of surgery. More importantly, this thesis hopes to raise questions and spark further discussions in the field of aneurysm surgery.